2018
DOI: 10.1002/da.22848
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance of youth with primary generalized anxiety disorder versus primary obsessive-compulsive disorder

Abstract: Background: Despite gains made in the study of childhood anxiety, differential diagnosis remains challenging because of indistinct boundaries between disorders and high comorbidity. This is certainly true for generalized anxiety disorder (GAD) and obsessive-compulsive disorder (OCD) as they share multiple cognitive processes (e.g., rumination, intolerance of uncertainty, and increased attention to threat). Disentangling such cognitive characteristics and, subsequently, underlying mechanisms could serve to info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Cognitive flexibility has therefore been proposed as one of the cognitive mechanisms underlying effective emotion regulation (Genet & Siemer, 2011;Ochsner & Gross, 2007). On the other hand, deficits in cognitive flexibility have been associated with trait anxiety and GAD, which are characterized by emotion dysregulation (Ansari, Derakshan, & Richards, 2008;Kim et al, 2019;Lee & Orsillo, 2014), although this has not always been replicated (Han et al, 2016). Executive functions rely on a prefrontalparietal network (Niendam et al, 2012) that partially overlaps with the neural circuits associated with HRV and emotion processing (Thayer et al, 2012), and this common corticosubcortical neural network may thus serve as the link between cognitive, emotional, and physiological processes.…”
mentioning
confidence: 99%
“…Cognitive flexibility has therefore been proposed as one of the cognitive mechanisms underlying effective emotion regulation (Genet & Siemer, 2011;Ochsner & Gross, 2007). On the other hand, deficits in cognitive flexibility have been associated with trait anxiety and GAD, which are characterized by emotion dysregulation (Ansari, Derakshan, & Richards, 2008;Kim et al, 2019;Lee & Orsillo, 2014), although this has not always been replicated (Han et al, 2016). Executive functions rely on a prefrontalparietal network (Niendam et al, 2012) that partially overlaps with the neural circuits associated with HRV and emotion processing (Thayer et al, 2012), and this common corticosubcortical neural network may thus serve as the link between cognitive, emotional, and physiological processes.…”
mentioning
confidence: 99%
“…The difference between OCDs and healthy controls was also significantly higher than that between GADs and the healthy group. This is consistent with Kim, Christensen and Ruggieri et al .’s () study on adolescents, which found that adolescents with OCD had impaired planning skills compared to GAD and healthy groups. The specific finding in this case was that it takes OCDs more time to solve the SOC stimulation task presented at multiple levels, and they require more actions.…”
Section: Discussionmentioning
confidence: 98%
“…Disturbance of the visuospatial WM suggests that OCD has disturbances in maintaining and controlling external information, similar results were found in previous study, but measured it with Cambridge Neuropsychological Automated Battery (CANTAB). 43 Myoinositol (MI) is located mainly in the glial cells of the brain, and is considered as a glial marker, and its content is believed to relate with glial cells proliferation. 44 , 45 It might participate in the protection against osmotic shock, signaling pathways, vesicle endocytosis and exocytosis.…”
Section: Discussionmentioning
confidence: 99%